NATO's next secretary general: Rasmussen's leadership legacy for Jens Stoltenberg. (2nd July 2016) - Hendrickson, Ryan C.
Abstract : Former Norwegian Prime Minister Jens Stoltenberg became NATO's secretary general on 1 October 2014, succeeding Anders Fogh Rasmussen. As NATO's leader, Rasmussen aggressively pushed this military alliance in new and challenging directions. He also viewed his leadership post in a fundamentally different way when compared to his predecessors. His legacy provides his successor with more opportunities to serve as a 'general', rather than solely as a 'secretary'. This article addresses Rasmussen's influence on the office of secretary general, and also examines two additional personality trait variables of previous NATO leaders that may shape Stoltenberg's term at the alliance's helm.